2012
DOI: 10.1080/10401334.2012.641482
|View full text |Cite
|
Sign up to set email alerts
|

Human Error and Patient Safety: Interdisciplinary Course

Abstract: The students showed improved knowledge and substantive skill level relative to patient safety and human error concepts. Working in interdisciplinary teams gave the students a better understanding of the role each discipline can have in improving health care systems and health care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Other common methodological limitations included poor response rates, 19 22 35 40 41 inadequate description of the course 19 39 and/or inadequate reporting of results. 22 28 29 33 Limitations relating to the assessment tools employed are described in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Other common methodological limitations included poor response rates, 19 22 35 40 41 inadequate description of the course 19 39 and/or inadequate reporting of results. 22 28 29 33 Limitations relating to the assessment tools employed are described in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past two decades, the patient safety movement has urged hospitals to improve the safety of their practices. 1–4 Although patients are frequently surveyed on the satisfaction of their experiences in hospital, these surveys do not capture information that can be used to improve safety of care. 5 Patients’ own perceptions of the care provided to them is an overlooked yet well-placed resource for understanding the factors responsible for safety of care.…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest obstacles to maintaining care quality relates to training of professionals (2) . The present review showed that higher education institutions have made efforts to create innovative curricula that are capable of incorporating patient safety and focused on prevention of mistakes that cause harm to patients, especially those related to HAIs (11)(12)(13)(14)(15)(16)(17)(18)(19) . To achieve this objective, institutions have resorted to instruments that facilitate the learning and retention of this topic, given that the traditional teaching method based on the "see one, do one, teach one" strategy is considered out-of-date, ineffective, Title/Subject category Database/ year Design Interventions Outcomes…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare-associated infections, including their principles, pathogenesis and transmission mechanisms, are part of the curriculum of health-related courses worldwide. Nevertheless, prevention and control of this type of infections as an indicator of quality and safety is little explored, even in medical school in developed countries (18)(19)(20)(21)(22)(23)25) . This is a consequence of overvaluing content that helps develop clinical skills, such as diagnosis, treatment, post-treatment and followup, to the detriment of actions oriented to quality and safety in processes related to patient care (24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation